Optimasi Rute Distribusi Bantuan Logistik Kesehatan ke Daerah Rawan Bencana Banjir di Kota Yogyakarta - Lukman Adhitama; Oktaviana Putri; Siti Dinar Rezki Ramadhani (Jagratara: Journal of Disaster Research, 2023)
In the context of flood risk mitigation in Yogyakarta City, particularly in the districts of Gondokusuman and Umbulharjo, this study highlights the significant impact of geographical factors and high rainfall intensity. Floods not only cause damage to infrastructure but also pose a serious threat to public health. Flood-prone areas often become breeding grounds for diseases that can spread rapidly, especially in emergency conditions. This research aims to identify optimal routes for the distribution of health logistics in dealing with flood disasters in Yogyakarta City. Using the Simulated Annealing (SA) algorithm, the study compares the optimization results of distribution routes without clustering and with clustering (based on districts). Findings indicate that the use of clustering is effective in minimizing the distance and travel time of distribution, with the clustering scenario emphasizing time efficiency. The contribution of this research lies in the development of responsive and efficient health distribution strategies during flood emergencies. Thus, the implementation of the SA algorithm and clustering can serve as a foundation for better emergency response planning, providing tangible benefits for those involved in flood disaster management in the region.